Kontribusi Pondok Pesantren Zawiyah Darussufi dalam Pengembangan Tarekan Tijaniyah di Garut 2008-2022 - Lida Hida; Asep Achmad Hidayat (Priangan: Journal of Islamic Sundanese Culture, 2023)
The entry into the Tijaniyah Order is not known for certain. In 1928, the Tijaniyah Order was already in Cirebon, West Java. Which at this time the Tijaniyah Order already had quite a number of followers and spread throughout Indonesia. In this study the authors used historical research methods. In this method there are 4 steps that must be carried out by the writer, namely heuristics, criticism, interpretation and historiography. the result of this research is the history of the Zawiyah Darussufi Islamic boarding school which was built in the middle of the Jatiputra Asri Cibunar housing complex, Tarogong Kidul, Garut Regency, West Java. The emergence of the Tijaniyah Order in Garut which experienced several leadership periods, and one of the contributions of the Zawiyah Darussufi Islamic Boarding School in the development of the Tijaniyah Order, namely by establishing a fathoniyah hostel which has a purpose other than a place of freedom or a safe place of worship, namely for a rehabilitation facility for Muslims who come from Pattani used to be a low standard drug user and other bad habits.Â